The Transformation of Thailand's Diplomatic Relations after the Bowring Treaty of 1855: From under the Chinese Diplomatic System to the Modern Diplomatic System - Kornphetcharat, Kotchaphop (UI Scholars Hub, 2025)
The Bowring Treaty of 1855, formally known as the Treaty of Friendship and Commerce between the British Empire and the Kingdom of Siam (now Thailand), marked a pivotal moment in Siam’s integration into the global economy. Prior to the treaty, Siam's international trade was primarily conducted under the Chinese tributary system, which significantly shaped its economic and diplomatic interactions. The 1855 treaty, however, dramatically shifted Siam's foreign relations by diminishing China’s dominance as the regional power and opening Siam to increased European influence and trade. This research delves into the multifaceted impact of the treaty on Sino-Thai relations, examining its consequences on individual, state, and systemic levels. It explores how the treaty transformed Thailand's political economy, altered the role and status of the Chinese community within Thailand, and produced both positive and negative effects on Sino-Thai relations. The study contends that the Bowring Treaty was instrumental not only in reshaping Siam’s economic landscape but also in altering the dynamics of Sino-Thai relations significantly.